EVIDENCE-BASED CASE REPORT (EBCR) PENCEGAHAN HYPOTERMI MENGGUNAKAN PLASTIK (Jurnal Kesehatan Siliwangi, 2022)
One of the causes of mortality in newborns, especially in LBW, is due to hypothermia. There are many methods for handling hypothermia in LBW, including the incubator method, the kangaroo method and the plastic bag method. The purpose of this study was to determine the effect of using plastic on low birth weight babies with low birth weight in preventing hypothermia. the research method is a journal study by searching articles using data based on Pubmeed and the Cochrane Library. Research results in this case the use of plastic to warm the baby is very influential. Where LBW and LBW at that time the temperature was 360C and after being wrapped in plastic, approximately 15 minutes later the temperature rose to normal at 36.90C. In line with the results of research from Valizadeh, Leila et al. that the results showed that the use of plastic covers was effective in regulating body temperature of premature infants 28-30 weeks of gestation and birth weight of 800-1250 g who were admitted to the NICU on the 2nd and 3rd day of hospitalization.